TECHNOLOGICAL innovations - Business Source Premier (Business Source Premier)
Here are entered works on fundamental technological improvements or changes in materials, production methods, processes, organization, or management which increase efficiency and production. Works on original devices or processes are entered under "Inventions."
Keywords: Sciences économiques; Thésaurus de base de données